Management of Perineal Massage in Pregnant Women as an Effort to Prevent Perineal Rupture in Vaginal Delivery (Literative Review) - Euvanggelia Dwilda Ferdinandus; Gusti Ayu Gita Maharani; Ratna Dwi Jayanti (Jurnal KESANS : Kesehatan dan Sains, 2022)
When approaching the time of delivery in the third trimester of pregnancy, pregnant women experience anxiety about the stigma that childbirth will hurt and injure the perineum,prevention of perineal rupture can be done by perineal massage. The method used in this research is to use a literature review study This discussion aims to collect and analyze articles to identify the effectiveness of perineal massage management as an effort to prevent rupture. Results In this discussion it was found that perineal massage has significant results in reducing the occurrence of perineal rupture. Perineal massage is also beneficial in reducing the rate of episiotomy as well as providing other benefits to the mother and the newborn. However, these studies have drawbacks, namely, this perineal massage does not yet have global clinical guidelines on the standard of implementing perineal massage, in some studies the sample experienced dropout in research and differences in research results that affect perineal massage on the prevention of perineal rupture. further research is needed regarding the standard of perineal massage and the support of husbands and midwives in education and implementation of perineal massage.